2018
DOI: 10.1007/s00262-018-2154-8
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol kinase α inactivation is an integral component of the costimulatory pathway that amplifies TCR signals

Abstract: The arsenal of cancer therapies has evolved to target T lymphocytes and restore their capacity to destroy tumor cells. T cells rely on diacylglycerol (DAG) to carry out their functions. DAG availability and signaling are regulated by the enzymes diacylglycerol kinase (DGK) α and ζ, whose excess function drives T cells into hyporesponsive states. Targeting DGKα is a promising strategy for coping with cancer; its blockade could reinstate T-cell attack on tumors while limiting tumor growth, due to positive DGKα f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Previous studies have demonstrated that DGKα and ζ play crucial roles in T cell development, activation, anergy, and survival, and CD8 T cell-mediated anti-viral immune responses, iNKT cell development, regulatory T cell differentiation, and anti-tumor immune responses (27,(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54). Additionally, DGKζ has been found to regulate B cell development (70), mast cell activation (71), TLR-mediated innate immunity (72), and NK cells (73).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that DGKα and ζ play crucial roles in T cell development, activation, anergy, and survival, and CD8 T cell-mediated anti-viral immune responses, iNKT cell development, regulatory T cell differentiation, and anti-tumor immune responses (27,(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54). Additionally, DGKζ has been found to regulate B cell development (70), mast cell activation (71), TLR-mediated innate immunity (72), and NK cells (73).…”
Section: Discussionmentioning
confidence: 99%
“…DGKα and ζ, isoforms that express at high levels in T cells, have been demonstrated to inhibit the activation of both Ras-Erk and PKCθ-NFκB cascades as well as mTOR signaling (35)(36)(37). They regulate conventional αβT cell, iNKT cell, mucosal associated invariant T cell, and regulatory T cell development, negatively control T cell activation, regulate CD8 T cell mediated anti-viral responses and activation induced T cell death, promote T cell anergy, and inhibit anti-tumor responses (27,(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55). However, the role of DGKs in T H differentiation is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, DGKα inhibition by Ritanserin induced cell death in glioblastoma stem cells and this was partially mediated by apoptosis [124]. Additionally, Ritanserin, as with other small molecule inhibitors of DGKα, also enhanced T cell signaling but failed to promote long-term T-cell activation [125].…”
Section: Targeting Dgks In Cancer Therapiesmentioning
confidence: 99%
“…Many of the negative regulators are less well-annotated in the canonical TCR signaling pathway, although functions have been assigned to some. Diacylglycerol (DAG) kinases, DGKA (rank 17) and DGKZ (rank 1)negative regulators of DAG-mediated signalswere both found to restrain human T cell proliferation following stimulation (Arranz-Nicolás et al, 2018;Gharbi et al, 2011). The E3 ubiquitin-protein ligase, CBLB (rank 4) and its interacting partner, CD5 (rank 12), work together to inhibit TCR activation via ubiquitination leading to degradation of the TCR (Voisinne et al, 2016).…”
Section: A Genome-wide Pooled Crispr Screen Uncovers Regulators Of Thmentioning
confidence: 99%